The Influence of service quality on customer trust through the perceived value of Bank Syariah in Langsa City - Syahputra, Rico (Institute of Computer Science (IOCS), 2024)
Banks have an important meaning for the economy. This research aims to determine the influence of service quality on trust through perceived value in Islamic banks. In this research, nonprobability sampling was used with the data collection method using the purposive sampling method. The population in this study were all residents of Langsa City who had savings at BS. The sample in this study was 100 people and analyzed the data using SEM-PLS. The research results show that service quality and perceived value have a positive and significant effect on trust. Perceived value successfully mediates the relationship between service quality and trust.